2015
DOI: 10.1158/0008-5472.can-14-2527
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tissue Injury Activates Satellite Cells and Promotes Sarcoma Formation via the HGF/c-MET Signaling Pathway

Abstract: Some patients with soft tissue sarcoma (STS) report a history of injury at the site of their tumor. While this phenomenon is widely reported, there are relatively few experimental systems that have directly assessed the role of injury in sarcoma formation. We recently described a mouse model of STS whereby p53 is deleted and oncogenic Kras is activated in muscle satellite cells via a Pax7CreER driver following intraperitoneal injection with tamoxifen. Here, we report that after systemic injection of tamoxifen,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
0
37
2
Order By: Relevance
“…We previously showed that some tumors generated by injection of tamoxifen into Pax7 Cre-ER-T2/+ ; Kras LSL-G12D/+ ; p53 FL/FL mice resembled human rhabdomyosarcoma (RMS) [15, 16]. Because NRAS is more commonly mutated in human RMS than KRAS [1719], we generated Pax7 Cre-ER-T2/+ ; Nras LSL-G12D/+ ; p53 FL/FL ; ROSA26 mTmG/mTmG (P7NP) mice to model mutations that more frequently occur in human RMS.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that some tumors generated by injection of tamoxifen into Pax7 Cre-ER-T2/+ ; Kras LSL-G12D/+ ; p53 FL/FL mice resembled human rhabdomyosarcoma (RMS) [15, 16]. Because NRAS is more commonly mutated in human RMS than KRAS [1719], we generated Pax7 Cre-ER-T2/+ ; Nras LSL-G12D/+ ; p53 FL/FL ; ROSA26 mTmG/mTmG (P7NP) mice to model mutations that more frequently occur in human RMS.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of soft tissue sarcomas arise in the limbs of older people although rhabdomyosarcoma, especially the embryonal subtype, tends to occur predominantly in young children [21]. Most soft tissue sarcomas arise sporadically but muscle injury, most likely by increasing the number of activated satellite cells, enhances the penetrance and shortens the latency of rhabdomyosarcoma phenotypes in mice [18,22]. In addition, known risk factors for the development of specific types of sarcoma in humans include exposure to radiation (e.g.…”
Section: Pathology Of Soft Tissue Sarcomasmentioning
confidence: 99%
“…Because the very character of each experiment results in tumorigenesis or no tumorigenesis, any untested variable may be the key between the 2 potential results. For example, elegant work by others has recently demonstrated that the sarcomagenesis-originating potential of satellite cells in particular depends on their activation in response to injury (37,38). Our experiments did not address the application of this principle to synovial sarcomagenesis, but future work should.…”
Section: Discussionmentioning
confidence: 94%